Quantitative expression of estrogen, progesterone and human epidermal growth factor receptor-2 and their correlation with immunohistochemistry in breast cancer at Uganda Cancer Institute. - Henry Wannume; Nixon Niyonzima; Sam Kalungi; Julius Boniface Okuni; Tonny Okecha; Edward Kakungulu; Steven Mpungu Kiwuwa; Geoffrey Waiswa; Sylvester Kadhumbula; Monica Namayanja; Martin Nabwana; Jackson Orem (PLoS ONE)
The detection of Estrogen Receptor (ER), Progesterone Receptor (PR), and Human epidermal growth factor receptor 2 (HER-2) is important for the stratification of breast cancer and the selection of therapeutic modalities. This study aimed to determine the quantitative expression of ER, PR and HER-2 using Immunohistochemistry and their correlation with quantitative baseline Ct values measured using Quantitative Polymerase Chain Reaction (PCR). This study also assessed the use of fresh breast tissue biopsies preserved in RNAlater solution in the quantitative detection of these receptors using PCR technique. The study evaluated 20 matched formalin fixed paraffin embedded and RNAlater preserved samples for ER, PR, and HER-2 using IHC and quantitative PCR technique. One portion of the breast tissue biopsy was fixed immediately in 10% neutral buffered formalin and another was preserved in RNAlater. After the histological confirmation of breast cancer by the H&E technique, formalin fixed paraffin embedded tissues (FFPE)-positive cases were matched with their corresponding RNAlater samples for IHC and qPCR. The extracted RNA was quantified using Nanodrop technology, resulting into complementary DNA. ER and PR using IHC were expressed in 60% (n = 12) of the study samples and were negative in 40% (n = 8) of samples. HER-2 was negative in 70% (n = 14) of study samples, 25% (n = 5) positive, and 5% (n = 1) equivocal. With the quantitative expression of ER, PR, and HER-2 being reported in the IHC triple-negative breast cancer cases. The mean Ct values for the hormonal receptors correlated with what has been previously studied with ER at 19.631, PR at 25.410 and HER-2 at 25.695. There was no statistically significant difference between the mean Ct values of RNAlater and FFPE with their P-values being 0.9919, 0.0896 and < 0.0001 for ER, PR, and HER-2 respectively. P-values; 0.9919 and 0.0896 for ER and PR respectively being greater than 0.05 it's a borderline significance although HER-2 had a statistical significance. With a concordance in the detection of these breast cancer hormonal receptors, qPCR can be used in our setting considering the delays that may be associated in following the samples through IHC processing.